Comparative Figurative Language Found in Maya Angeluo Poems - Jas, Paulinus; Candra, Komang Dian Puspita; Utami, Ni Made Verayanti (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2023)
The objective of this study focus on types of comparative figurative language in the poem Maya Angeluo and their meaning. In resolving the problem of the study. The study for analyzed used the theory from Kennedy (1983), with the book entitled Literature: An introduction to Fiction : Poetry and Drama, and the theory of meaning ussed from Leech (1981), with the book entitled semantics : The study of Meaning. this study was used to describe the meaning of the types figurative language found in Maya Angeluo poems. This study used the data source from Maya Angeluo poems. Documentation method was used to collect data. This study used qualitative descriptive method has beed used to describe the data to analyzed the data, whereeas formal and informal method has been used to present the finding. There was found 21 data of types figurative language from 12 in poem Maya Angleuo. The meaning of those 21 comparative figurative language was describe useing the theory of Leech (1981). There was found two types of meaning were found from the data. They were affective meaning and connotative meaning. Keywords: figurative language, types, meaning, maya angeluo